2022
DOI: 10.3389/fpls.2022.994306
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nitrogen use efficiency through agronomic and molecular based approaches in cotton

Abstract: Cotton is a major fiber crop grown worldwide. Nitrogen (N) is an essential nutrient for cotton production and supports efficient crop production. It is a crucial nutrient that is required more than any other. Nitrogen management is a daunting task for plants; thus, various strategies, individually and collectively, have been adopted to improve its efficacy. The negative environmental impacts of excessive N application on cotton production have become harmful to consumers and growers. The 4R’s of nutrient stewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 269 publications
(357 reference statements)
0
9
0
Order By: Relevance
“…Additionally, nitrogen inhibitors, the split application of nitrogen, irrigation time, and the correct placement method of fertilizer which takes into consideration soil and crop type could improve NUE [ 93 , 94 , 95 , 96 ]. Therefore, melatonin must be studied more widely in the agronomic field in order to be considered a possible input into the NUE strategy [ 12 , 16 , 97 ], including the effects of enhancement by melatonin in the assimilation and metabolization of nitrogen, especially in symbiotic plants [ 54 , 55 ]. It is also important to study the effect of melatonin on rhizosphere and its microbiome, on which there are already some promising data [ 87 , 88 , 89 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nitrogen inhibitors, the split application of nitrogen, irrigation time, and the correct placement method of fertilizer which takes into consideration soil and crop type could improve NUE [ 93 , 94 , 95 , 96 ]. Therefore, melatonin must be studied more widely in the agronomic field in order to be considered a possible input into the NUE strategy [ 12 , 16 , 97 ], including the effects of enhancement by melatonin in the assimilation and metabolization of nitrogen, especially in symbiotic plants [ 54 , 55 ]. It is also important to study the effect of melatonin on rhizosphere and its microbiome, on which there are already some promising data [ 87 , 88 , 89 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of synthetic N fertilizers rather than symbiotic N fixation resulted in poor N use efficiency (Lassaletta et al, 2014). Likewise, uncontrolled flood irrigation resulted in NO 3 − leaching due to a negative charge and high solubility; furthermore, it creates anoxic conditions which lead to the development of denitrifying microorganisms (Chattha et al, 2022;Shabbir et al, 2022). Environmental factors, mainly higher temperature and wind speed, increase the risk of NH 3 volatilization (Chattha et al, 2022).…”
Section: Management Factorsmentioning
confidence: 99%
“…Likewise, uncontrolled flood irrigation resulted in NO 3 − leaching due to a negative charge and high solubility; furthermore, it creates anoxic conditions which lead to the development of denitrifying microorganisms (Chattha et al, 2022;Shabbir et al, 2022). Environmental factors, mainly higher temperature and wind speed, increase the risk of NH 3 volatilization (Chattha et al, 2022). It was found that an increase in soil temperature due to climate change increases the nitrification rate resulting in N loss and poor NUE (Engel et al, 2011).…”
Section: Management Factorsmentioning
confidence: 99%
See 2 more Smart Citations